METTL3‐m6A methylase regulates the osteogenic potential of bone marrow mesenchymal stem cells in osteoporotic rats via the Wnt signalling pathway. Issue 5 (25th April 2022) - Wu, Tianli; Tang, Hui; Yang, Jianghua; Yao, Zhihao; Bai, Long; Xie, Yuping; Li, Qing; Xiao, Jingang
Abstract: Objectives: Bone marrow mesenchymal stem cells (BMSCs) hold a high osteogenic differentiation potential, but the mechanisms that control the osteogenic ability of BMSCs from osteoporosis (OP‐BMSCs) need further research. The purpose of this experiment is to discuss the osteogenic effect of Mettl3 on OP‐BMSCs and explore new therapeutic target that can enhance the bone formation ability of OP‐BMSCs. Materials and Methods: The bilateral ovariectomy (OVX) method was used to establish the SD rat OP model. Dot blots were used to reveal the different methylation levels of BMSCs and OP‐BMSCs. Lentiviral‐mediated overexpression of Mettl3 was applied in OP‐BMSCs. QPCR and WB detected the molecular changes of osteogenic‐related factors and Wnt signalling pathway in vitro experiment. The staining of calcium nodules and alkaline phosphatase detected the osteogenic ability of OP‐BMSCs. Micro‐CT and histological examination evaluated the osteogenesis of Mettl3 in OP rats in vivo . Results: The OP rat model was successfully established by OVX. Methylation levels and osteogenic potential of OP‐BMSCs were decreased in OP‐BMSCs. In vitro experiment, overexpression of Mettl3 could upregulate the osteogenic‐related factors and activate the Wnt signalling pathway in OP‐BMSCs. However, osteogenesis of OP‐BMSCs was weakened by treatment with the canonical Wnt inhibitor Dickkopf‐1. Micro‐CT showed that the Mettl3 (+) group had an increased amount of new bone formation at 8 weeks. Moreover, the results of histological staining were the same as the micro‐CT results. Conclusions: Taken together, the methylation levels and osteogenic potential of OP‐BMSCs were decreased in OP‐BMSCs. In vitro and in vivo studies, overexpression of Mettl3 could partially rescue the decreased bone formation ability of OP‐BMSCs by the canonical Wnt signalling pathway. Therefore, Mettl3 may be a key targeted gene for bone generation and therapy of bone defects in OP patients. Abstract : In this study, the osteoporosis rat model was successfully established by OVX. OP‐BMSCs were successfully isolated and cultured from the femur of OP rat. Lentiviral‐mediated overexpression of Mettl3 could partially rescue the impaired osteogenic ability of OP‐BMSCs by activating the canonical Wnt signalling pathway in vitro and in vivo .